Linking Turkish Credit Card Market as Two-Sided Market - Dilek, Serkan; Ulucay, Korkmaz; Simsek, Lutfi (Elsevier BV, 2012)
AbstractCredit Card markets are special kind of market which is called as Two-Sided Markets in economics literature. In these markets there are two sides which benefit from the number of subscribers on other sides. Although scholars and economists has given importance and examined two-sided markets since the beginning of 21th century Turkish scholars have not interested much about these markets. We studied Turkish Credit card market by using Two-sided markets approach and also we aimed to contribute literature that is poor about Turkey Two-Sided Markets. We defined actors and competition structure in Turkish credit card markets and explained profit functions of them and set profit maximizing problems.
Keywords: Network Externality; Two-Sided Markets; Competition Between Banks; Credit Card Market